Philosophy, literature, and politics essays honoring Ellis Sandoz - Embry, Charles R., 1942-; Cooper, Barry, 1943-; Sandoz, Ellis, 1931- (University of Missouri Press, 2005)
"Festschrift honoring Ellis Sandoz, director of the Eric Voegelin Institute for American Renaissance Studies and editor of Collected Works of Eric Voegelin. Essays explore philosophy, literature, and politics, and focus on Xenophon, Natsume, Freud, Robert Penn Warren, and George Santayana"--Provided by publisher.